ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP AKTIVITAS PENGIRIMAN BARANG DENGAN METODE FOB DESTINATION POINT PADA PT. SIANTAR TOP TBK MEDAN - Riska Novia Dani; Nur Fadhilah Ahmad Hasibuan (Universitas Muhammadiyah Metro, 2023)
The implementation of an information system that is not good can occur when the task arrangements for each department are confused, where order information should only be changed by the sales and logistics department but it turns out that it can also be done by other departments resulting in a discrepancy in goods sales data. This problem can affect other departments that receive sales information and can also result in dissatisfaction with customers who have trusted the company. This study uses descriptive qualitative methods, so it can be concluded that the utilization of the bookkeeping data framework to the transportation of products in the logistics division of PT. Siantar Top, Tbk Medan is not very good and not in accordance with the functional norms of the organization, because there are still errors in the data framework guidelines, especially those related to goods delivery activities.